The symbolic intersecting ableism and racism scale - Friedman, Carli (Frontiers in Rehabilitation Sciences, 2025)
IntroductionIntersectionality recognizes and maps the ways oppressions interact and intersect for multiply marginalized people. This framework is a pushing back against the historical approach to discrimination that has taken a “single-axis” view of discrimination, focusing on one single type of oppression, even for people with multiple identities. Little attention has been drawn to intersectionality when it comes to disability, especially related to disability and race.ObjectiveIn recognition of the intersectional nature of ableism and racism, the aim of this study was to develop and validate the Symbolic Intersecting Ableism and Racism Scale (SIARS).Materials and methodsWe piloted the SIARS with 512 people (July-October 2024) and conducted an exploratory factor analysis to examine the underlying structure of the SIARS.ResultsThe SIARS has adequate validity and reliability. Our findings suggest the SIARS is comprised of a complex combination of a denial of continuing discrimination, individualism, and empathy. The findings also indicated many points of contention with the single-axis symbolic ableism scale measure, which examines disability only, further reinforcing the need to measure and attend to intersectionality.ConclusionWithout doing so, we will never truly be able to dismantle oppression and discrimination, including the ableism disabled people face.